EXPLORING ENGLISH TEACHING TECHNIQUE USED FOR YOUNG LEARNERS - rohmania hanum; Fajarina Maskhurin (Teaching English as Foreign Language, Literature and Linguistics, 2023)
This research aims to explore the importance of teaching English to young learners. Currently, English language education is not limited to high schools but also extends to young learners' education, both in Indonesia and in other countries. In fact, it is more advantageous to begin learning English at a young age because young learners are in their golden age, during which their memory is exceptionally sharp, facilitating the memorization and learning of new concepts. Prioritizing English language education for young learners is crucial as it equips children with the proficiency in English language skills required for their subsequent levels of education. The research methodology used in this study includes observation, documentation, interviews, and field notes. The results of this research indicate that the process of teaching English to young learners involves a structured lesson plan arranged by the tutor and language materials provided by the Oxford University Press. Teaching techniques for young learners include cooperative learning, the direct method, total physical response, the grammar-translation method, and drilling. Effective teaching media for young learners include flashcards and educational games. Challenges in teaching English to young learners include crowded classrooms, limited individual attention, and complexity. However, supportive factors include creating an English-immersive environment.